Type 1 Responses of Human Vγ9Vδ2 T Cells to Influenza A Viruses - Qin, Gang (American Society for Microbiology, 2011)
γδ T cells are essential constituents of antimicrobial and antitumor defenses. We have recently reported that phosphoantigen isopentenyl pyrophosphate (IPP)-expanded human Vγ9Vδ2 T cells participated in anti-influenza virus immunity by efficiently killing both human and avian influenza virus-infected monocyte-derived macrophages (MDMs) in vitro. However, little is known about the noncytolytic responses and trafficking program of γδ T cells to influenza virus. In this study, we found that Vγ9Vδ2 T cells expressed both type 1 cytokines and chemokine receptors during influenza virus infection, and IPP-expanded cells had a higher capacity to produce gamma interferon (IFN-γ). Besides their potent cytolytic activity against pandemic H1N1 virus-infected cells, IPP-activated γδ T cells also had noncytolytic inhibitory effects on seasonal and pandemic H1N1 viruses via IFN-γ but had no such effects on avian H5N1 or H9N2 virus. Avian H5N1 and H9N2 viruses induced significantly higher CCL3, CCL4, and CCL5 production in Vγ9Vδ2 T cells than human seasonal H1N1 virus. CCR5 mediated the migration of Vγ9Vδ2 T cells toward influenza virus-infected cells. Our findings suggest a novel therapeutic strategy of using phosphoantigens to boost the antiviral activities of human Vγ9Vδ2 T cells against influenza virus infection.